Bubble continuous positive airway pressure therapy for neonatal respiratory distress at birth in level III newborn unit in Chengalpattu Medical College Hospital: a prospective observational study - R., Diana Grace; S., Suresh Kumar; ., Sathya (International Journal of Contemporary Pediatrics, 2019)
Background: Bubble continuous positive airway pressure (bCPAP), a non-invasive respiratory device provides continuous pressure that helps recruitment of more alveoli, increases the lungs, functional residual capacity and decreases the work of breathing in newborns admitted with respiratory distress. Bubble continuous positive airway pressure (bCPAP) is the most important respiratory support in different types of respiratory conditions in level III. In this observational study, author reported this research using bCPAP therapy as the primary respiratory support in level III unit in tertiary care centre in Chengalpattu, Tamil Nadu, India. Despite reporting their indications, duration of use and adverse effects we tried to search for further improvement in other areas of CPAP therapy in level III newborn unit. Methods: This prospective observational study included 250 babies delivered in obstetric unit and admitted with respiratory distress within 6 hours of birth at level III care. They were treated according to level III newborn unit protocol. Those data were collected and entered in the proforma. Newborns were followed up till discharge. Results: A total of 250 babies satisfying the inclusion criteria delivered in Chengalpattu Medical College Hospital, Tamil Nadu, India (mean gestational age 36±2 weeks, mean birth weight 2.5±1.2 kg were included. All newborns were given bCPAP as the primary support. The most common underlying cause of respiratory distress was transient tachypnea of newborn (44%), followed by respiratory distress syndrome (24%) and prolonged respiratory transition (18%). The therapy success rate was 86%. Only 35 newborns failed to respond to CPAP. The most common adverse effect was eye puffiness (19%). Conclusions: Bubble continuous positive airway pressure (b CPAP) therapy use is being well established in level III unit for various respiratory conditions with minimal failure and adverse effects. Its use in extreme preterms and initiation after 6 hours is controversial.